(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Hemoglobin of the mother during pregnancy is well established to be contributors to abnormal prenatal development and pregnancy outcomes. Objectives:To study the effect of maternal anemia on anthropometric measurement of full term newly born babies. Methods:Two hundred pregnant women at time of delivery were investigated for their Hemoglobin. Their newborns were investigated for anthropometric measurement (weight, length, head circumference and chest circumference) immediately after birth. The questionnaire involved questions about age, parity, economy, educational level, and antenatal care of the mothers, and also sex, gestational age, anthropometric measures (weight, length, head circumference and chest circumference) and outcomes of the newborns. Results:From 200 pregnant women who were included in our study, 115 (57.5%) of them delivered by normal vaginal delivery and 85 (42.5%) delivered by caesarian section. Sixty (30%) of mothers were anemic. Five (2.5%) of the newborns were small for gestational age all of them from anemic mothers. Conclusion:Anemia affects neonatal outcomes in full term babies; full term babies of anemic mothers were in the normal anthropometric range, but they were much lower than babies of normal mothers. Keywords:Pregnancy, Anemia, Small for gestational age